Psycho-emotional booster` kinesiological module: benefits for psychomotor fitness of 11-13-year-old racing skiers - Golovko, D. E. (Theory and Practice of Physical Culture, 2020)
Objective of the study was to rate and analyze benefits of a new `Psycho-emotional booster` kinesiological module training system to improve psychomotor fitness of the 11-13 year old cross-country racing skiers.